STUDENTS’ ATTITUDE TOWARD THE USE OF INTERNET IN ENGLISH CLASSROOM - Mesi Oktavia; Reflinda Reflinda; Absharini Kardena (Universitas Mahaputra Muhammad Yamin, 2020)
Related literature indicates that the internet has an important role and great potential in language learning. It is also obvious that the attitudes of students affect the learning process significantly. This research aimed to find out the students’ attitude toward the use of the internet in English classrooms. The design of this research was survey research in which the sample was collected from 37 students at SMK Pembangunan Bukittinggi which used simple random sampling as the technique sampling of the research. Additionally, the analysis of the data was done by identifying the respondent’s responses, analyzing the data, and making a conclusion. The result showed that the mean score of students’ attitudes toward the use of the internet in the cognitive aspect was 3.7. It means that the students had a positive attitude in the cognitive aspect. Besides, the mean score of students’ attitudes toward the use of the internet in terms of the affective was 3.3. It means the students had a positive attitude toward the use of the internet in terms of affective. In addition, the mean of the conative attitude statement was 3.4. It means the students had a positive attitude in the conative aspect related to the use of the internet.